Pengaruh Kepribadian, Lingkungan Keluarga Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Manajemen Universitas Jambi - Ariyanto Ariyanto; Agus Sholikin; Novita Ekasari (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This research is a research that focuses on Personality, Family Environment and Entrepreneurship Education on Entrepreneurial Interests of Jambi University students. The type of research used is empirical research with quantitative data analysis. This study aims to determine the influence of personality, family environment and entrepreneurship education on the entrepreneurial interest of management students at Jambi University. The population in this study were management students 2016-2018 Jambi University. The data used in this study is primary data data obtained directly from respondents. The results of this study indicate that there is a significant influence from the variables of personality, family environment and entrepreneurship education on the entrepreneurial interest of Jambi University management students.